The impact of foot reflexology on fatigue and sleep quality in school-aged children undergoing hemodialysis - Amal Hashem Mohamed; Mostafa Shaban; Huda Hamdy Mohammed; Randa Mohamed Abobaker; Salman Hamdan Alsaqri; Rania Abd-Elnaby Mohammed Allam (Wolters Kluwer Medknow Publications, 2024)
Objective: This study aimed to evaluate the effects of foot reflexology on fatigue and sleep quality in school-aged children receiving hemodialysis. Methods: A quasi-experimental pretest-posttest design was utilized. Thirty children of ages 6-12 undergoing in-center hemodialysis were recruited. The Pittsburgh Sleep Quality Index (PSQI) and Inventory of Fatigue Symptom (IFS) scales were administered at baseline. Participants then received 30 min of foot reflexology massage before hemodialysis sessions 3 days per week for 12 weeks. Posttest administration of the sleep and fatigue scales occurred after the intervention period. Results: Reflexology massage led to significant improvements in sleep quality components, including duration (0%-30% normal sleepers), efficiency (0%-50% >85%), latency (50%-0% >60 min), disturbances, and daytime dysfunction. The mean PSQI score decreased from 18.2 to 9.7 (P < 0.05). Fatigue severity substantially decreased, with the mean IFS score improving from 105.7 to 64.1 (P < 0.05). Conclusion: Foot reflexology is an effective nursing intervention for reducing fatigue and improving sleep quality in children on hemodialysis, warranting integration into routine care.